Eco-Compensation in China’s Evolving Environmental Management Regime : Ecological Protection and Water Pollution Control in the Yangtze River Basin - World Bank (World Bank, Washington, DC, 2021)
The Yangtze river and the economic belt it defines are central to China’s economy, yet they face severe environmental challenges. The river plays a major role in the historical, cultural, and political identity of China, and is a key driver of the country’s economy. It is one of the world’s most biodiverse regions, with ecosystems and natural resources that underpin national water, food, and energy security. Yet over the past four decades, the Yangtze river basin has experienced large-scale, high-intensity development that has severely impacted ecological and hydrological conditions. The region is emblematic of the challenges China faces as it looks to transition toward higher quality green development. This policy note, reviews experiences with eco-compensation in the Yangtze river economic belt (YREB) and makes recommendations for enhancing outcomes. Specifically, the note: (1) provides an overview of the development progress of eco-compensation schemes in the YREB in support of the national strategy for ecological protection and green development in the YREB; (2) assesses the effectiveness of the current eco-compensation schemes in the YREB through a series of case studies; and (3) presents policy recommendations for improving eco-compensation schemes in the YREB.